The Influence of Corporate Culture on Audit Practices and Ethics - Sonjaya, Yaya (Golden Ratio of Auditing Research, 2024)
This study investigates the influence of corporate culture on audit practices and ethics, aiming to understand the mechanisms, challenges, and implications of cultural factors in shaping auditors' behaviors within organizational contexts. The research utilizes a qualitative approach, drawing on existing literature and theoretical frameworks to analyze the complex interplay between corporate culture and auditing practices. Through a comprehensive review, the study identifies key cultural dimensions, including leadership style, organizational values, communication patterns, and ethical norms, that significantly influence auditors' experiences and behaviors. Findings reveal that auditors operating within organizations characterized by strong ethical cultures demonstrate higher levels of ethical sensitivity, professionalism, and adherence to professional standards, while those in environments with weak cultures may face pressures compromising their independence and integrity. Theoretical perspectives such as agency theory, stakeholder theory, and social identity theory are employed to elucidate the mechanisms underlying these relationships. The implications of the study underscore the importance of fostering a strong ethical culture, incorporating cultural assessments into audit engagements, and investing in resources and technologies to mitigate ethical risks effectively. By understanding how corporate culture influences audit practices and ethics, stakeholders can work collaboratively to promote integrity, accountability, and transparency within the auditing profession, thereby enhancing public trust and confidence.